Development Strategy for a Tourism Village Based on Natural and Cultural Potential in Lambanapu Village, East Sumba Regency - Wijayanti, Ani; Yulianto, Atun (Media Wisata, 2026)
Village tourism has become one of the strategic approaches to promoting local economic development based on natural and cultural resources. Lambanapu Village in East Sumba Regency represents an area with distinctive tourism potential that has not yet been optimally developed. This study aims to formulate a development strategy for a tourism village based on natural and local cultural potential through a focused and sustainable approach. The research employed a descriptive qualitative method, with data collected through field observations, in-depth interviews, and documentation. The data were analyzed using SWOT analysis, IFAS, EFAS, and the IE Matrix techniques. The findings indicate that Lambanapu Village possesses significant strengths, including natural attractions such as Tanau Hill and Seribu Hill, rich cultural assets such as traditional dances and woven handicrafts, and the initial participation of the local community in tourism activities. However, several challenges remain, including limited infrastructure, inadequate public facilities, and insufficient human resource training, which hinder further development. Based on the strategic position in Quadrant I (Grow and Build), the development direction of the village is oriented toward a vertical integration strategy through strengthening infrastructure, enhancing community capacity, developing thematic tourism products, and fostering institutional collaboration. With an integrated and participatory strategy, Lambanapu Village has considerable potential to become a leading tourism destination in East Sumba while generating economic benefits and preserving cultural and environmental sustainability..